Pharmacotherapy efficacy assessment in arterial hypertension with metabolic disturbances - A. A. Demin; O. M. Medvedeva; I. A. Bondar (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To assess efficacy of various pharmacotherapy schemes in arterial hypertension (AH) with metabolic disturbances (MD). Material and methods. Open, randomized, comparative study in 3 parallel groups, including 90 patients with Stage I-II AH and MD, was performed. Group 1 was administered moxonidine and eprosartan; Groups 2 and 3 – standard monotherapy (diuretic, beta blocker, calcium antagonist, plus ACE inhibitor in case of low effectiveness); Group 3 additionally received a lipase inhibitor orlistat. Results. Eight weeks later, target BP level was achieved in 86% patients from Group 1, 73% – from Group 2, and 57% - from Group 3. In Group 3, body mass index decreased by 5.3%, and waist circumference – by 3.5%. Total cholesterol level reduced in Groups 1 (by 7.3%) and 3 (by 9.6%). In Group 1, basal immunoactive insulin level declined by 25.2%. Fasting glycemia reduced in Groups 1 and 3 – by 6.3% and 8.6%, respectively. In Group 1, basal cortisol level decreased by 26.3%. All medications were well tolerated. Conclusion. Imidazoline receptor antagonist was more effective than standard therapy: despite compatible antihypertensive effects, moxonidine improved metabolic parameters. Adding orlistat to antihypertensive treatment improved metabolic parameters and 24-hour BP profile in patients with AH and MS.